A Novel Soundproof Ventilation Plant Design with High Performance and No Energy Consumption. (27th August 2015) - Yu, Ya-Lin; Chao, Yu-Tin; Lee, Lai-Chung; Yen, Jia-Yush; Fan, Yun-Chiu
Abstract : This paper proposes an advanced approach for designing soundproof windows with good ventilation. The structure of this study is based on three acoustics theorem and can reduce noise and ventilate the space at the same time. Using this structure on wall can help also avoid noise interference effect indoors and increase air quality. This study uses plants as appropriate soundproof structure to improve carbon dioxide content for providing better living environment. Simulations of the sound field and CFD demonstrate that the structure has good performance on noise reduction and effect of ventilation.